Presencia de microplásticos en la playa de San Jacinto de la provincia de Manabí - Ecuador - Gómez Garcés, Sindy Elizabeth (2023)
The main objective of this research was to evaluate the presence of microplastics on the beach in San Jacinto-Manabí-Ecuador. The study area was divided by georeferencing into 3 zones (tourist, fishing and less intervention), taking 72 sand samples and 36 water samples and then proceeding to the extraction of microplastics, identifying and quantifying them through observation. The results show that the area with the highest presence of microplastics is the fishing area, with a predominance of the fiber type with 48%; in the other two areas, the film type predominated with 84% in the area of less intervention and 54% in the tourist area. The sizes found were mostly equivalent to 1 mm with 492 elements, 2 mm with 497 elements and 5 mm with 605 elements. Finally, the results were socialized with the beach dwellers who showed interest in the problem raised in this research, committing themselves to care for the beach and minimize the consumption of plastics.